PERLAWANAN TERHADAP DISKRIMINASI AGAMA GOLONGAN AHMADIYAH DALAM NOVEL MARYAM KARYA OKKY MADASARI - Vina Damayanti (Universitas Muhammadiyah Surakarta, 2023)
The Novel Maryam by Okky Madasari tells the story of a religious conflict that causes discrimination, expulsion, and injustice to the Ahmadiyya group. This novel was published in 2012 by winning the Khatulistiwa Literary Award. Okky Madasari is a novelist who is known for his writings that contain social criticism aimed at certain people. His writing started from his story and experience of discrimination against minority groups. The purpose of this study is to discuss the resistance to religious discrimination of the Ahmadiyya group. This study uses a descriptive qualitative method to understand social phenomena from the participant’s point of view or perspective in order to provide data, opinions, and thoughts. The data source of this research is Maryam’s Novel with reading, analyzing, and note-laking techniques related to the issues to be raised. This can be seen from the content of the discussion, namely: 1) the resistance of the leaders to discrimination against the Ahmadiyah Group in society, namely as a form the Ahmadiyah group against discrimination, namely the attitude of the Ahmadiyah community against a group of people when the expulsion occurred, some of them were Maryam figures and Khairuddin; 2) resistance against government officials regarding the Ahmadiyya group caused by the attitude of Islamic organizations that brand Mirza Ghulam Ahmad’s followers as a misleading group and the issuance of the MUI Fatwa that Ahmadiyah is a heretical group.Keywords: Maryam, Okky Madasari, Ahmadiyah, discrimination.